Sistem Penentuan Penerima Bantuan Pendidikan Gratis Menggunakan PCA dan FAHP - Jasril Jasril; M Irsyad; Iis Afrianty (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2012)
One program management agency is distributing zakat free educational assistance (Sekolah Juara)for prospective elementary school students and junior high school. Problems in this free education aid,many criteria must be considered as well as the determination of the potential recipients of the group wasnot able to (very poor and poor). This study uses Principal Component Analysis to categorize recipientsinto three groups: very poor, poor and not poor. Furthermore, the very poor and poor sorted to obtainsequence receiver using Fuzzy Analitycal Hierarchical Process. There are 7 criteria and 4 poor groupingcriteria used for determining as a result of the decision. The results of calculations can be concluded thatthe application of the method Principal Component Analysis and Fuzzy Hierarchical Process Analitycalmulticriteria problems can be taken, as in the case of classification and determination of free educationalassistance Sekolah Juara.Keywords: Fuzzy Analitycal Hierarchical Process, Principal Component Analysis